Minimal Bratteli diagrams and the dimension groups of AF C*-algebras - Ryan J. Zerr (International Journal of Mathematics and Mathematical Sciences)
A method is described which identifies a wide variety of AF algebra dimension groups with groups of continuous functions. The results here generalize the well-known fact that commutative AF algebras have dimension groups which can be identified with groups of integer-valued continuous functions.